Locally-Induced CaMKII Translocation Requires Nucleotide Binding - Fitzgerald, Zachary T.; Rose, Jacqueline K. (Frontiers in Synaptic Neuroscience, 2020)
Calcium-calmodulin-dependent protein kinase (CaMKII) is a molecule involved in several cell processes including plasticity related to learning and memory. Activation of NMDA-type glutamate receptors results in translocation of CaMKII to synapses. However, there are at least two distinct mechanisms by which glutamate-dependent CaMKII translocation occurs: one well-studied process resulting from whole-cell glutamate stimulation and one resulting from brief, local glutamate application. Unlike the relatively fast CaMKII translocation seen following whole-cell glutamate delivery (seconds), local application results in CaMKII translocation that occurs gradually within 6–10 min. This locally-induced translocation of CaMKII requires L-type Ca2+ channel co-activation but does not rely on GluN2B receptor subunit expression, unlike translocation following whole-cell application of glutamate. The current study examined if nucleotide binding is necessary for locally-induced CaMKII translocation, similar to CaMKII translocation resulting from whole-cell glutamate application. Three different mechanisms of inhibition were employed: staurosporine (ATP inhibitor), CaMKII(281–302) peptide inhibitor and expression of the K42M mutation. Locally-induced CaMKII translocation was moderately suppressed in the presence of either the broad-spectrum kinase inhibitor staurosporine (100 nm) or the CaMKII(281–302) peptide inhibitor. However, expression of the catalytically dead K42M mutation that prevents ATP-binding to CaMKII, significantly inhibited locally-induced translocation. Thus, CaMKII translocation following brief, local glutamate application requires nucleotide binding, providing support for future research into the molecular mechanisms of this distinct form of CaMKII translocation.